Determinan Indeks Saham Syariah di Indonesia dan Malaysia - Zety Nasyatia; M. Nur Rianto Al Arif (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2019)
Islamic stock indices are influenced by many factors, both domestic and foreign. This study tried to test the determinants of Islamic stock indexes in Indonesia and Malaysia. Using data in the 2012-2017 periods, this study found that there were several factors that influenced the Islamic stock index in Indonesia and Malaysia. World gold prices and the Dow Jones Islamic Market (DJIUS) affect sharia stock indices in both Indonesia and Malaysia. For the world oil price variable only affects the Islamic stock index in Malaysia, but not in Indonesia. While the inflation rate has no effect on sharia stock indexes in Indonesia and Malaysia. This finding has important implications for determining policies related to the Islamic capital market.